The Submandibular Musculature of Phyllomedusinae (Anura: Hylidae): A Reappraisal - Faivovich, J.; Baeta, D.; Vera Candioti, F.; Haddad, Celio Fernando Baptista [UNESP]; Tyler, M. J. (Wiley-Blackwell, 2011)
The submandibular musculature of 37 species of the five currently recognized genera of the subfamily Phyllomedusinae (Anura: Hylidae) is described; observations are made on the variation and ontogeny of these muscles. Supplementary apical elements of the m. intermandibularis occur in all phyllomedusines studied, in addition to the supplementary posterolateral elements previously reported. Our observations are discussed in the context of 1) the proposed homology between supplementary apical and posterolateral elements; 2) the homology with the apical elements reported for Pelodryadinae (sister taxon of Phyllomedusinae); and 3) the implications for our understanding of the relationships between Phyllomedusinae and Pelodryadinae. Anatomical differences between the apical and posterolateral elements and their co-occurrence in phyllomedusines indicate that these supplementary elements are not homologous. Despite differences between phyllomedusines and pelodryadines in the adhesion of supplementary fibers to the principal element of the m. intermandibularis and the occurrence of a broad aponeurosis or a medial raphe, the extensive morphological and developmental resemblances of the apical elements indicate that these structures are homologous, and that the presence of apical elements is a synapomorphy of Phyllomedusinae + Pelodryadinae. J. Morphol. 272: 354-362, 2011. (C) 2011 Wiley-Liss, Inc.
Keywords: Phyllomedusinae; Pelodryadinae; submandibular; musculature; anatomy; systematics; supplementary elements